El aula virtual y su influencia en el rendimiento académico de álgebra lineal II, con los estudiantes de sexto semestre de Ciencias Exactas de la Universidad Nacional de Chimborazo, periodo octubre 2015-enero 2016 - Allauca Sandoval, Norma Isabel (2016)
The present study was developed in two stages. The first stage: a bibliographic research about web platforms, virtual classrooms, educative topics, learning theories, pedagogical models, and academic performance of the students as well as the evaluation of the learning process. The second stage: a field research that applied surveys to students and educators about the use of virtual classroom in the teaching and learning process of Lineal Algebra II. This research emerged from the need to diagnose whether virtual classroom affect the academic performance of the students with the aim to change and improve the educational system not only in Exact Sciences but also on every major in order to train future professionals in education to develop their skills in a modern and competitive society. This is a correlational and descriptive study which was conducted to students enrolled in the sixth semester, school of Exact Sciences at the University of Chimborazo, from October 2015 to January 2016. The relationship between the use of virtual classroom and the effects in the students’ academic performance was obtained through the analysis of the most important characteristics and features of virtual classroom that immediately us to know the problem.